Peran Organisasi (Pelajar Pondok Pesantren Modern Babussalam) dalam Menumbuhkan Nilai-Nilai Kedisiplinan Santri di MTS Pondok Pesantren Modern Babussalam - Ayu Gustira; Nurmisda Ramayani (Lembaga Pengembangan Kinerja Dosen, 2023)
Lack of awareness of students and peers in the value of civility at the MTS Modern Babussalam Islamic Boarding School. The method used in this research is qualitative research, collecting data by observation, interviews and documentation. The collected data was then analyzed by qualitative analysis. The results obtained from this study are: First, the role of the Babussalam Modern Islamic Boarding School Student Organization (OPPM-Bs) in Growing the Disciplinary Values ​​of Santri at Babussalam Modern Islamic Boarding School MTs as an organizational vessel, the Role of Babussalam Modern Islamic Boarding School Student Organization (OPPM- BS) in Cultivating Santri Discipline Values ​​at Babussalam Modern Islamic Boarding School MTs as a motivator, Role of Babussalam Modern Islamic Boarding School Student Organizations (OPPM-BS) in Growing Santri Discipline Values ​​at Babussalam Modern Islamic Boarding School MTs as student coaches. Second, Factors supporting the role of Modern Babussalam Islamic Boarding School Student Organizations (OPPM-Bs) in Growing Santri Discipline Values ​​at Babussalam Modern Islamic Boarding School MTs, including: Internal Factors (Family) and Environmental Factors